Biologically active sulphur rich volatiles of Allium stracheyi and their molecular docking studies against 5IBS: Sulphur rich volatiles of Allium stracheyi - Bisht, Balam Singh; Singh, Darshan; Karki, Gunjan; Vishwakarma, Mahesh Chandra; Rawat, Himanshu (Journal of Spices and Aromatic Crops, 2025)
Allium stracheyi, an endemic species of the Himalayan region, is part of the diverse Allium genus, known for its medicinal, nutritional, and aromatic properties. This research investigates the volatile constituents of Allium stracheyi, which contribute to its characteristic aroma, flavor, and potential therapeutic properties. Gas chromatography-mass spectrometry (GC-MS), was used to identify and characterize the volatile organic compounds (VOCs) present in this species. sulphur-containing compounds, especially trisulfide dipropyl, tetrasulfide dipropyl, dipropyl disulfide and trisulfide methyl propyl were the predominant constituents, accompanied by several aldehydes, alcohols, and hydrocarbons. To assess the potential bioactivity of these compounds, molecular docking studies were carried out using the 5IBS protein (chain A), a crystal structure of a target enzyme involved in a biological pathway. The 5IBS protein was selected for its relevance to inflammatory and microbial processes. The docking results demonstrated significant binding affinities of the sulphur-containing volatiles to the active site of the 5IBS A chain, indicating a possible inhibitory mechanism. 1-allyl-2-isopropyldisulfane and disulfide, 1-(1-propenylthio) propyl propyl exhibited a notable docking score of -3.5 kcal/mol. This study suggests that sulphur-rich compounds from Allium stracheyi could serve as promising candidates for the development of natural antimicrobial and anti-inflammatory agents. Further in vitro and in vivo studies are warranted to explore these bioactivities and understand the therapeutic potential of these volatiles.